Концептуалізація соціальності права в сучасних інтегративних парадигмах: П.Бурд’є, Ю.Габермас, Е.Гідденс - Сердюк, О.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2007)
Новая методологическая ситуация в социальном познании формулирует не только теоретические
и мировоззренческие проблемы, но и варианты их конструктивного решения. Появление в последней
четверти 20 века интегративных социологических концепций открывает перспективы непротиворечивого объяснения соотношения объективного и субъективного в праве. The new methodological situation in the social research causes not only theoretical and world-outlook
issues but also variants of their constructive solutions. The appearance of integrative sociological concepts in
the last quarter of the 20th century presents perspectives of clear explainations of the objective and the subjective in law.